Overall survival with maintenance olaparib in platinum-sensitive relapsed ovarian cancer by somatic or germline BRCA and homologous recombination repair mutation status - Pignata, Sandro; Oza, Amit; Hall, Geoff; Pardo, Beatriz; Madry, Radoslaw; Cibula, David; Klat, Jaroslav; Montes, Ana; Glasspool, Rosalind; Colombo, Nicoletta; Pete, Imre; Herrero Ibáñez, Ana; et al. (British journal of cancer, 2025)
BACKGROUND: The open-label, single-arm, multicentre ORZORA trial (NCT02476968) evaluated maintenance olaparib in patients with platinum-sensitive relapsed ovarian cancer (PSR OC) with a germline (g) or somatic (s) BRCA1 and/or BRCA2 mutation (BRCAm) or a non-BRCA homologous recombination repair mutation (non-BRCA HRRm). METHODS: Patients were in response to platinum-based chemotherapy after ≥2 prior lines of treatment and underwent prospective central screening for tumour BRCA status, then central gBRCAm testing to determine sBRCAm or gBRCAm status. An exploratory cohort evaluated non-BRCA HRRm in 13 predefined genes. Patients received olaparib 400 mg (capsules) twice daily until investigator-assessed disease progression. Secondary endpoints included overall survival (OS) and safety. RESULTS: 177 patients received olaparib. At the final data cutoff (25 June 2021), median OS from study enrolment was 46.8 (95% confidence interval [CI] 37.9-54.4), 43.2 (31.7-NC [not calculated]), 47.4 (37.9-NC) and 44.9 (28.9-NC) months in the BRCAm, sBRCAm, gBRCAm and non-BRCA HRRm cohorts, respectively. No new safety signals were identified. CONCLUSION: Maintenance olaparib showed consistent clinical activity in the BRCAm and sBRCAm cohorts; exploratory analysis suggested similar activity in the non-BRCA HRRm cohort. These findings highlight that patients with PSR OC, beyond those with gBRCAm, may benefit from maintenance olaparib.
Keywords: protein BRCA2; Humans; lidé středního věku; Recombinational DNA Repair; Phthalazines; BRCA1 Protein; zárodečné mutace; Female; Aged; dospělí; nádory vaječníků; Ovarian Neoplasms; senioři; lidé; PARP inhibitory; Poly(ADP-ribose) Polymerase Inhibitors; Adult; ftalaziny; Germ-Line Mutation; ženské pohlaví; Middle Aged; protein BRCA1; piperaziny; Piperazines; BRCA2 Protein; lokální recidiva nádoru; rekombinační oprava DNA; Neoplasm Recurrence, Local